Fibro Sarcoma of the Gingiva: A Rare Presentation - Mamun, Md Talal; Rob, Chowdhury Foyzur (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Fibrosarcoma is a rare malignant mesenchymal neoplasm’s of the fibroblasts which are represents 1% of all malignancies in the head and neck region. In this article we described a case of primary fibrosarcoma of the gingiva in right sided alvulas of the mandible in 16 years old male. Who was presented with a rapidly growing painful lump. Microscopically the tumor mass was composed with atypical proliferation of spindle cells arranged in intersecting fascicles and sterioform pattern. In immunohistochemically the cells showed immuno-reactivity for SAM, while negativity towards the others markers. On the basis of clinical histological and immunohistochemistry our case was diagnosed as a low grade primary fibrosarcoma of gingiva. We performed radical resection with wide margin as a primary treatment of choice without neck dissection. After primary treatment there is no signs of recurrence and metastasis was observed last 3 years follow up. J Bangladesh Coll Phys Surg 2022; 40: 310-313